Алгебра,Буду благодарна Всем добра♥

Алгебра,Буду благодарна Всем добра♥
Гость
Ответ(ы) на вопрос:
Гость
[latex] \frac{15}{ x^{2}-6x+9 } - \frac{2}{x-3} = 1 \\ \frac{15}{ (x-3)^{2} } - \frac{2}{x-3} = 1 \\ \frac{15}{ (x-3)^{2} } - \frac{2(x-3)}{(x-3)(x-3)} = 1 \\ [/latex] [latex] \frac{15-2(x-3)}{ (x-3)^{2} } = 1 \\ \frac{15-2x+6}{ (x-3)^{2} } = 1 \\ [/latex] [latex] \frac{21-2x}{ (x-3)^{2} } = 1 \\ (x-3)^{2} = 21-2x \\ x^{2} -6x+9 + 2x - 21 = 0 \\ [/latex] [latex] x^{2} - 4x - 12 = 0 \\ x_{1} = 6, x_{2} = -2 \\ [/latex] Ответ:  -2 ;  6.
Не нашли ответ?
Ответить на вопрос
Похожие вопросы